Reconstructing himmah from Ibn al-Qayyim al-Jawziyyah's thought: Toward a contemporary Islamic education paradigm - Ari Mulyono; Khaerudin (Eduvista: Journal of Education and Innovation, 2026)
Contemporary Islamic education faces challenges in strengthening students' spiritual orientation, while studies on himmah have largely treated it as a moral and spiritual concept rather than reconstructing it as an educational paradigm. This study aims to reconstruct the concept of himmah in the thought of Ibn al-Qayyim al-Jawziyyah and transform it into a paradigm for contemporary Islamic education. A qualitative library research approach was employed by analyzing Ibn al-Qayyim al-Jawziyyah's major works through concept identification, thematic categorization, and conceptual synthesis. The findings reveal that himmah constitutes a spiritual driving force comprising five interconnected dimensions: Spiritual Orientation, Diligence in Deeds, Inner Hijrah, Self-Control, and Prophetic Exemplification. These dimensions are reconstructed into an educational paradigm that contributes to character formation, discipline and istiqāmah, self-regulated learning, and digital literacy. This study contributes to the discourse on Islamic education by proposing a conceptual framework that bridges Ibn al-Qayyim al-Jawziyyah's intellectual legacy with the needs of contemporary Islamic education. Abstrak Pendidikan Islam kontemporer menghadapi tantangan dalam memperkuat orientasi spiritual peserta didik, sementara kajian mengenai himmah masih cenderung dipahami sebagai konsep moral dan spiritual sehingga belum banyak direkonstruksi sebagai paradigma pendidikan. Penelitian ini bertujuan mengonstruksi konsep himmah dalam pemikiran Ibn al-Qayyim al-Jawziyyah serta mentransformasikannya menjadi paradigma pendidikan Islam kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kepustakaan melalui analisis terhadap karya-karya utama Ibn al-Qayyim al-Jawziyyah menggunakan tahapan identifikasi konsep, kategorisasi tematik, dan sintesis konseptual. Hasil penelitian menunjukkan bahwa himmah merupakan kekuatan spiritual yang tersusun atas lima dimensi utama, yaitu Spiritual Orientation, Diligence in Deeds, Inner Hijrah, Self-Control, dan Prophetic Exemplification. Kelima dimensi tersebut direkonstruksi menjadi paradigma pendidikan yang berkontribusi terhadap pembentukan karakter, disiplin dan istiqāmah, self-regulated learning, serta literasi digital. Penelitian ini memperluas diskursus pendidikan Islam dengan menawarkan kerangka konseptual yang mengintegrasikan warisan intelektual Ibn al-Qayyim al-Jawziyyah dengan kebutuhan pendidikan Islam kontemporer.